Wheat Variety-Specific Response to Seeding Rate Under Intensive Management Conditions in Western Kansas in 2021–2022 - R. P. Lollato; N. Giordano; L. Ryan; L. M. Simão; J. A. Romero Soler; L. O. Pradella (Kansas Agricultural Experiment Station Research Reports, 2023)
Wheat response to seeding rate is variable and depends on resource availability during the growing season (e.g., fertility, moisture, and temperature). Our objective was to evaluate winter wheat population and grain yield responses to seeding rate and its interaction with variety in a highly-managed production system where manageable stresses were limited. This study was established to evaluate the response of the wheat varieties Joe, WB-Grainfield, Langin, and LCS Revere to five seeding rates ranging from 200,000 to 1,000,000 seeds per acre. The site was managed by growers who consistently win state and national wheat yield contests near Leoti, KS. The trial was established on September 25, 2021, after a long summer fallow in sorghum residue. A total of 0.75-in. rainfall surrounding sowing ensured good stand establishment. The entire growing season was dry, limiting grain yield to the 40 to 66 bu/a range, depending on treatment. There were significant effects of seeding rate and variety on stand count, with no interaction. Main effects suggested that the stand count increased with increases in the seeding rate (from 205,795 to 658,544 plants per acre), with the 800,000 and 1,000,000 seeds/a rates attaining the highest stands. WB-Grainfield had the greatest population (522,586 plants per acre), which was statistically greater than that of Langin (412,121 plants per acre) but similar to the other two varieties with intermediate population. Final populations were closer to the target population at lower seeding rates as compared to higher seeding rates. Grain yield also depended primarily on variety and on seeding rate, with no interaction between both effects. Grain yield ranged between 56.9 and 58.2 bu/a acre for the seeding rates ranging between 600,000 and 1,000,000 seeds/a, and from 49.3 to 55.0 bu/a for lower seeding rates. Langin and WB-Grainfield were the highest yielding varieties (57.6 bu/a), and LCS Revere and Joe had the lowest yield (53.1 bu/a). These results suggest that wheat grain yield responses to seeding rate were not dependent on variety, with optimum seeding rates as low as 600,000 seeds/a. We note that increasing seeding rates beyond 600,000 seeds/a led to numerical but not statistical increases in yield.
Keywords: seeding rate; intensive management; yield contest; winter wheat; stand establishment; plant density; grain yield